2021
DOI: 10.1002/jbt.22848
|View full text |Cite
|
Sign up to set email alerts
|

LINC00511 facilitates Temozolomide resistance of glioblastoma cells via sponging miR‐126‐5p and activating Wnt/β‐catenin signaling

Abstract: Temozolomide (TMZ) is the first-line chemotherapy drug for glioblastoma (GBM) but acquired TMZ resistance is frequently observed. Thus, a TMZ resistant GBM cell line U87-R was established to search for potential long noncoding RNAs (lncRNAs) used in TMZ resistance. In our study, LINC00511 was identified as a TMZ resistanceassociated lncRNA in U87-R cells by transcriptome RNA sequencing. The potential functions of LINC00511 were evaluated by quantitative real-time polymerase chain reaction, cell viability assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 50 publications
0
13
0
Order By: Relevance
“…Studies found that LINC00511 acted as a competing endogenous RNA (ceRNA) with NFIA (Nuclear Factor I A) to bind with miR-29c-3p, revealing the LINC00511/miR-29c-3p/NFIA axis as potential therapeutic targets for CRC treatment [ 33 , 34 ]. In a study on temozolomide (TMZ), the first-line chemotherapy drug for glioblastoma (GBM), LINC00511 expression upregulation correlated with the poor prognosis of GBM patients and LINC00511 silencing impaired the tolerance of TMZ, while its overexpression increased the TMZ resistance of sensitive GBM cells [ 35 ]. In addition to this, the silencing of LINC00511 expression suppressed cell viability, proliferation, migration, and invasion, and accelerated the apoptosis of glioma cells via a suggested miR-15a-5p/AEBP1 axis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies found that LINC00511 acted as a competing endogenous RNA (ceRNA) with NFIA (Nuclear Factor I A) to bind with miR-29c-3p, revealing the LINC00511/miR-29c-3p/NFIA axis as potential therapeutic targets for CRC treatment [ 33 , 34 ]. In a study on temozolomide (TMZ), the first-line chemotherapy drug for glioblastoma (GBM), LINC00511 expression upregulation correlated with the poor prognosis of GBM patients and LINC00511 silencing impaired the tolerance of TMZ, while its overexpression increased the TMZ resistance of sensitive GBM cells [ 35 ]. In addition to this, the silencing of LINC00511 expression suppressed cell viability, proliferation, migration, and invasion, and accelerated the apoptosis of glioma cells via a suggested miR-15a-5p/AEBP1 axis [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that LINC00511 expression is increased in temozolomide‐resistant GBM cells compared with that of parental cells and is associated with a low OS rate in patients with GBM. The resistance mechanism is that LINC00511 sponges miR‐126‐5p and activates the Wnt/β‐catenin signalling pathway 98 . RNA methylation modification (m6A) is the most usual modification in eukaryotic mRNAs 99 .…”
Section: Long Non‐coding Rnasmentioning
confidence: 99%
“…A literature search revealed various lncRNAs affecting TMZ resistance in glioma, as well as their functions and targets ( 62 - 82 ). This list of lncRNAs is presented in Table I .…”
Section: Oncogenic Lncrnas Promote Tmz Resistance In Gliomasmentioning
confidence: 99%
“…The silencing of lncRNA miR-155 host gene (MIR155HG) expression was previously reported to promote glioma sensitivity to TMZ through the Wnt/β catenin pathway by inhibiting poly-pyrimidine tract-binding protein 1 expression ( 64 ). Furthermore, the knockdown of LINC00511 expression enhanced the sensitivity of U87-R glioma cells to TMZ by targeting miR-126-5p and activating Wnt/β-catenin signaling ( 82 ). It has also been previously reported that EGFR signaling plays a key role in GBM ( 85 ), by regulating lncRNA nuclear enriched abundant transcript 1 (NEAT1) expression and in turn promoting glioma cell growth by targeting the Wnt/β-catenin pathway.…”
Section: Oncogenic Lncrnas Promote Tmz Resistance In Gliomasmentioning
confidence: 99%